Crystal Structure of Inorganic Pyrophosphatase From Schistosoma japonicum Reveals the Mechanism of Chemicals and Substrate Inhibition - Wu, Qun-Feng; Wang, Wei-Si; Chen, Shen-Bo; Xu, Bin; Li, Yong-Dong; Chen, Jun-Hu (Frontiers in Cell and Developmental Biology, 2021)
Soluble inorganic pyrophosphatases (PPases) is significant for facilitating the growth and development of organisms, which makes it an attractive functional protein. To provide insight into the molecular basis of PPases in Schistosoma japonicum (SjPPase), we expressed the recombinant SjPPase, analyzed the substrate metabolism to inorganic pyrophosphate (PPi) and measured its activity. Moreover, we solved the crystal structure of SjPPase in complex with orthophosphate (Pi) and processed the docking of PPi and methylene diphosphonic acid (MDP) into the active site. Our results suggest that the SjPPase possesses the PPi hydrolysis activity and the activity declines with increase in inhibitors. However, the enzyme shows substrate inhibition properties unexpectedly. Through PPi metabolic pathway analysis, the physiological action of substrate inhibition might be energy-saving, adaptable cytoprotection and biosynthetic rate-regulating. Furthermore, the structure of apo-SjPPase and SjPPase with Pi has been solved at 2.6 Å and 2.3 Å, respectively. The docking of PPi into the active site of this complex has revealed that substrate inhibition may result from attacking PPi into SjPPase F intermediate in catalytic cycle. Our results provide novel insights into the physiological function of PPase in organisms without PPi transporter and the mechanism of its substrate inhibition.